Near-roadway air pollution associated with COVID-19 severity and mortality – Multiethnic cohort study in Southern California. (December 2021) - Chen, Zhanghua; Huang, Brian Z.; Sidell, Margo A.; Chow, Ting; Eckel, Sandrah P.; Pavlovic, Nathan; Martinez, Mayra P.; Lurmann, Fred; Thomas, Duncan C.; Gilliland, Frank D.; Xiang, Anny H.
Highlights: Near-roadway air pollution (NRAP) exposure is a risk factor of COVID-19 severity. Non-freeway NRAP is a main contributor to the adverse effect in Southern California. The effect of NRAP is independent of regional PM2.5 and NO2 exposure. The associations are consistent across age groups, sex, and race/ethnicity. Abstract: Background: Air pollution exposure has been associated with increased risk of COVID-19 incidence and mortality by ecological analyses. Few studies have investigated the specific effect of traffic-related air pollution on COVID-19 severity. Objective: To investigate the associations of near-roadway air pollution (NRAP) exposure with COVID-19 severity and mortality using individual-level exposure and outcome data. Methods: The retrospective cohort includes 75, 010 individuals (mean age 42.5 years, 54% female, 66% Hispanic) diagnosed with COVID-19 at Kaiser Permanente Southern California between 3/1/2020–8/31/2020. NRAP exposures from both freeways and non-freeways during 1-year prior to the COVID-19 diagnosis date were estimated based on residential address history using the CALINE4 line source dispersion model. Primary outcomes include COVID-19 severity defined as COVID-19-related hospitalizations, intensive respiratory support (IRS), intensive care unit (ICU) admissions within 30 days, and mortality within 60 days after COVID-19 diagnosis. Covariates including socio-characteristics and comorbidities were adjusted for in the analysis. Result: One standard deviation (SD) increase in 1-year-averaged non-freeway NRAP (0.5 ppb NOx ) was associated with increased odds of COVID-19-related IRS and ICU admission [OR (95% CI): 1.07 (1.01, 1.13) and 1.11 (1.04, 1.19) respectively] and increased risk of mortality (HR = 1.10, 95% CI = 1.03, 1.18). The associations of non-freeway NRAP with COVID-19 outcomes were largely independent of the effect of regional fine particulate matter and nitrogen dioxide exposures. These associations were generally consistent across age, sex, and race/ethnicity subgroups. The associations of freeway and total NRAP with COVID-19 severity and mortality were not statistically significant. Conclusions: Data from this multiethnic cohort suggested that NRAP, particularly non-freeway exposure in Southern California, may be associated with increased risk of COVID-19 severity and mortality among COVID-19 infected patients. Future studies are needed to assess the impact of emerging COVID-19 variants and chemical components from freeway and non-freeway NRAP.